Pharmacological evidence supporting a role for IL-1, IL-2 and serotonin in the inflammation induced by Schistosoma mansoni Soluble Egg Antigen (SEA) in rat paws - C. M. F. Pacheco; C. A. P. Tavares; P. M. Z. Coelho; O. A. Rocha; J. M. M. Santos; F. R. M. Prado; J. N. Francischi (Mediators of Inflammation)
This study intended to characterize pharmacologically the mediator(s ) released in the inflammation induced by Soluble Egg Antigen (SEA), the main antigen released from eggs of Schistosoma mansoni, in rat hindpaws . A single intraplantar injection of 0.1–100 μg SEA at day zero induced a dose-dependent increase in the volume of rat hindpaws characterizing an oedema of quick onset (within 15 min) and 4 h-duration, which was confirmed by his topathological analys is of the paws . A second injection of SEA in the same paw (1–10 μg) 28 days later induced an increased dose -dependent oedematogenic response. The early oedematogenic response following SEA sensitization was derived from serotonin release and interleukin-1 (IL-1), since treatment with either pizotifen or anantibody against IL-1, reduced the response by 60% and 48%, respectively. The increased oedematogenic response derived from SEA-challenge (10 μg) of rat paws derived from a local rather than systemic reaction, since it was not observed if the sensitization was in the contralateral paw or the peritoneal cavity of the animals. Chronic tre atment with inhibitors of IL-2 synthesis / release such as cyclosporin or dexamethasone during the sens itization phase reduced the oedematogenic response due to SEA challenge by 51% and 55%, respectively. These data suggested that SEA-challenge was immune-derived and dependent of IL-2 release. It is discussed the association between cytokine release and the resistance of rats to S. mans o ni infe ction.